2022
DOI: 10.1002/hup.2856
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews of the acute effects of amphetamine on working memory and other cognitive performances in healthy individuals, with a focus on the potential influence of personality traits

Abstract: Objectives This research aimed to systematically review the acute effects of amphetamine (AMP), a dopamine‐releasing agent, on working memory (WM) and other cognitive performances. The investigation also aimed to review the impact of personality traits on the subjective and objective effects of AMP and possible links between personality traits and effects of AMP. Methods Previous double‐blind controlled studies assessing the main effects of AMP on WM and other cognitive performances in healthy volunteers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 223 publications
0
6
0
Order By: Relevance
“…Studies have shown that the objective or subjective effects amphetamine would be linked to between‐person variations in personality measures (Corr & Kumari, 2000; for review, see Kassim, 2022; Kelly et al., 2006; Kirkpatrick et al., 2013; see also White, 2017). For example, a study showed that subjective effects of three different doses of dexamphetamine (5, 10 and 20 mg) in healthy individuals were associated with individual differences in personality trait (Kirkpatrick et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the objective or subjective effects amphetamine would be linked to between‐person variations in personality measures (Corr & Kumari, 2000; for review, see Kassim, 2022; Kelly et al., 2006; Kirkpatrick et al., 2013; see also White, 2017). For example, a study showed that subjective effects of three different doses of dexamphetamine (5, 10 and 20 mg) in healthy individuals were associated with individual differences in personality trait (Kirkpatrick et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some studies that did not find effects of amphetamine on SWM, other studies did detect effects of amphetamine SWM ([ 6 , See 12 for review, 16 , 17 , 19 , 22 , 107 , 108 ]). We show that d-amphetamine also indirectly influences SWM, based on PLE score.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies (except one [ 31 ]) that used digit span tasks (DST) to examine verbal WM (VWM) reported that d-amphetamine did not affect performances on DST. The findings indicate that DST is not a sensitive tool to detect the effects of d-AMP on WM, ([for review, see 12 ]). In addition, there were no differences in effects of d-amphetamine that used either forward, backward or both tasks of the DS, which again implies that the recall direction is not sensitive to detect the effects of d-amphetamine on WM [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations